Access to the child: right or responsibility? - Abd Malek, Normi (INSI Publications, 2012)
Many a times, a custody proceeding will usually follow a divorce proceeding. If the custody of a child is given to one party, the other party will usually be given access or the opportunity to see or visit the child. A question arises as to whether this access is solely a right or at the same time a responsibility on the part of the parents. If it is a right, whether it is an absolute or limited right? Are there situations or circumstances where a parent might not be allowed to exercise his or her right? What if the children themselves refuse to see their parent? This paper will examine the above issues from both the civil and Islamic law perspectives. The emphasis will be on Malaysian law but comparison will be made to other jurisdictions such as English and Scottish.